1965
DOI: 10.3181/00379727-120-30677
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulonephritis in Pressor Drug-Enhanced Serum Sickness of Rabbits.

Abstract: In a recent investigation(1) it was found that repeated intravenous injections of blood pressure elevating drugs following a single large intravenous injection of horse serum in rabbits regularly caused marked enhancement of the lesions of serum sickness and the appearance of manifestations, such as verrucous endocarditis and acute synovitis, not ordinarily seen in this experimental condition. Glomerulonephritis when present was unusually severe but its incidence was not significantly increased.In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1969
1969
1988
1988

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Firstly, it is a well-known fact that the progres sion of renal disease is enhanced if the blood pressure is poorly controlled [2]. Secondly, animal studies indicate that renal damage in experimental immune complex nephritis is more severe if hypertension is induced in the animals at the same time [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, it is a well-known fact that the progres sion of renal disease is enhanced if the blood pressure is poorly controlled [2]. Secondly, animal studies indicate that renal damage in experimental immune complex nephritis is more severe if hypertension is induced in the animals at the same time [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Giese (1 4) has shown that during experimentally induced angiotensin hypertension the vascular lesions appear in the areas of dilated arterioles and that increased permeability to plasma components and possibly ischemia of the vascular wall are important in this context. The lesions of experital serum sickness are aggravated by high blood pressure (38). This may explain why immune complex nephritis together with DOCA-NaCI load exceeds the glomerular and vascular tolerance, resulting in irreversible injury.…”
Section: Discussionmentioning
confidence: 99%
“…' Although it was not stated just how glomerulonephritis was prevented, their conclusion clearly associated glom erular pressure, transit of complexes through vascular walls, and the development of glomerulonephritis without involving inflammatory reactions, fibrin deposition, anti basement membrane antibody or any other external fac tor. The importance of vascular pressure had been shown earlier [35] when it was shown that immune complex de position was enhanced in animals treated with pressor agents, and as a result glomerulonephritis of increased severity developed. Natural models of the effects of the lowered intrarenal blood pressure which follow renal ar tery obstruction have been described.…”
Section: Response Of Glomerular Components To Persistent Deposition Omentioning
confidence: 98%